Pengaruh Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan yang Dimediasi oleh Struktur Modal: Studi Kasus pada Perusahaan Sub Sektor Makanan dan Minuman - Nanda Apriliya; Alfiana Alfiana; Hanif Rani Iswari (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze tehe effect of profitability and firm size on firm value with capital structure as a mediating variable. The study was conducted on food and beverage sub-sector companies listed on the Indonesia Stock Exchange during 2020-2023. The variables used in this study include Return on Assets (ROA), frim size (SIZE), Dept to Equity Ratio (DER), and Price to Earnings Ratio (PER). Path analysis was applied to test the relationsips. The results show that booth profitability and firm size significantly influence capital structure. Pprofitability and firm size also directly affect firm value. Furthemore, capital structure ppartially mediates the relationship between profitabilitiy, firm size, and firm value. These findings highlight the importance of strategic capital structur management to enhance corporate financial performance and long-term value, especially in the food and beverage sector.